Apomixis for no bacteria-induced thelytoky in Diglyphus wani (Hymenoptera: Eulophidae) - Du, Sujie; Ye, Fuyu; Xu, Shiyun; Liang, Yongxuan; Wan, Fanghao; Guo, Jianyang; Liu, Wanxue (Frontiers in Genetics, 2023)
Abstract: In Hymenoptera species, the reproductive mode is usually arrhenotoky, where haploid males arise from unfertilized eggs and diploid females from fertilized eggs. However, a few species reproduce by thelytoky, where unfertilized eggs that develop into diploid females. Diploid females can be derived through various cytological mechanisms in thelytokous Hymenoptera species. However, these mechanisms were revealed mainly in those thelytokous Hymenoptera species infected by the bacterial reproductive regulator. In contrast, thelytokous Hymenoptera species of which reproductive manipulator has not been verified or excluding several common endosymbionts were paid less attention in their cytological mechanisms, for instance, Diglyphus wani (Hymenoptera: Eulophidae). Here, we investigated the cytological mechanism of D. wani using cytological methods and microsatellite markers. Our observations indicated that the diploid karyotypes of two strains of D. wani consist of four pairs of relatively large metacentric chromosomes and one pair of short submetacentric chromosomes (2n = 10). The arrhenotokous strains could complete normal meiosis, whereas the thelytokous strain lacked meiosis and did not expulse any polar bodies. This reproductive type of lacking meiosis is classified as apomictic thelytoky. Moreover, a total of 636 microsatellite sequences were obtained from thelytokous D. wani, dominated by dinucleotide repeats. Microsatellite markers results showed all three generations of offspring from thelytokous strain maintained the same genotype as their parents. Our results revealed that D. wani is the first eulophid parasitoid wasp in Hymenoptera whose thelytoky was not induced by bacteria to form an apomictic thelytoky. These findings provide a baseline for future inner molecular genetic studies of ameiotic thelytoky.